Pelacakan Perahu Masyarakat Yang Mengalami Kondisi Darurat Di Perairan Sipora Utara Kab. Kepulauan Mentawai Berbasis Internet Of Things - Ataul Mujib; Ramiati Ramiati; Rikki Vitria (Teknik Elektro Politeknik Negeri Padang, 2022)
Technology in search and rescue has been growing at this time, especially in early detection systems. Basarnas as the leading sector in search and rescue, has used an early detection communication tool called Radio Beacon to quick response search and rescue for aircraft and ship accidents, and conditions that endanger humans. However, in its application in the field, this early detection system has not been touched by the local community, especially because the price is still relatively expensive and the socialization of the importance of safety itself has not been maximized in the community. From these problems, this paper designs a tracking device that works like a Radio Beacon where the switch will activate the Arduino device, GPS module and SIM800l module. The GPS module receives the location coordinates to be further processed by Arduino and sent using the SIM800l module to Firebase and notifications is received by the smartphone and the location can be monitored through an android application created using the MIT App Inventor platform. From the test results, it is found that the initial data transmission process starts from the switch is activated until the notification is received by the smartphone, a delay of 70 seconds occurs while in the process of repeating sending data there is a delay between 10-35 seconds from what has been set in the program looping every 50 seconds.